2019
DOI: 10.1038/s41378-019-0047-4
|View full text |Cite
|
Sign up to set email alerts
|

Stretchable, self-healing, transient macromolecular elastomeric gel for wearable electronics

Abstract: Flexible and stretchable electronics are emerging in mainstream technologies and represent promising directions for future lifestyles. Multifunctional stretchable materials with a self-healing ability to resist mechanical damage are highly desirable but remain challenging to create. Here, we report a stretchable macromolecular elastomeric gel with the unique abilities of not only self-healing but also transient properties at room temperature. By inserting small molecule glycerol into hydroxyethylcellulose (HEC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 34 publications
0
25
0
1
Order By: Relevance
“…[ 14–16 ] For example thiol‐disulfide exchange reactions(disulfide metathesis), [ 17,18 ] Diels‐Alder reactions, [ 19 ] or Boron‐oxygen bonding. [ 20 ] It has a nondynamic covalent bond, for example, hydrogen bonding, [ 21–24 ] metal–ligand coordination. [ 25,26 ] Judit et al.…”
Section: Introductionmentioning
confidence: 99%
“…[ 14–16 ] For example thiol‐disulfide exchange reactions(disulfide metathesis), [ 17,18 ] Diels‐Alder reactions, [ 19 ] or Boron‐oxygen bonding. [ 20 ] It has a nondynamic covalent bond, for example, hydrogen bonding, [ 21–24 ] metal–ligand coordination. [ 25,26 ] Judit et al.…”
Section: Introductionmentioning
confidence: 99%
“…Nano-and microscale organic-organic interfaces for obtaining stretchability have been studied in the following areas; control of the permanent or dynamic bonds between two molecules in a homogeneously mixed state, [58][59][60] control of the dynamic bonding in the functional nanodomains where microphase separation is present, [63,64] adjusting the dynamic interaction between the functional nanodomains and the matrix, [67][68][69][70][71] creating strong interface between the organic matrix and the nanofibrils which is advantageous for securing stretchability due to its long contour path, [62,[73][74][75][76][77][78] and adjusting the interaction between infinitely long organic nanofibers and the organic matrix. [82][83][84] This section introduces some outstanding works for the different interfacial aspects.…”
Section: Design Of Nano/microscale Organic-organic Interfacesmentioning
confidence: 99%
“…Hao et al inserted low-molecular-weight glycerol in hydroxyethylcellulose to create hydrogen bonds between the polymer chains, and they formed a macromolecular gel with a high stretchability ( ≈ 300%) and the self-healing performance. [59] Kang et al reported a supramolecular polymer film constructed with a network of crosslinked polymer chains having both strong and weak hydrogen bonding units. [60] The strong hydrogen bonding units formed elastic nanodomains, and the weak bonding units dissipated the energy through the breakage of the bonds.…”
Section: Design Of Nano/microscale Organic-organic Interfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 20,21 ] On the other hand, for the development of advanced technologies like human–machine interfaces, the creation of new electronic devices and components having human‐like multifunctional properties is more critical. In general, the combination of electroconducting, stretching, and self‐healing abilities is a promising direction to meet the criteria for developing advanced technologies and applications, including soft robotics, [ 22,23 ] wearable healthcare electronics, [ 24–29 ] electronic/artificial skin and skin‐like electronics, [ 30–38 ] energy harvesting, and energy storage devices. [ 39–43 ]…”
Section: Introductionmentioning
confidence: 99%